Embedding Indigenous Mbojo Values in Project-Based Learning: A Quasi-Experimental Study in Elementary Sustainability Education - Ida Mawaddah; Sudarsono Sudarsono; Heriyanto Heriyanto (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2026)
Education for sustainable development at the elementary level still prioritizes cognitive knowledge over behavioral and attitudinal competencies, producing students who describe sustainability principles without enacting them in daily economic life. In Bima City, indigenous Mbojo values bearing on economic responsibility are largely absent from classroom practice, and no study has empirically examined a Mbojo-based Project-Based Learning (PjBL) model. This study tested whether the model strengthened sustainable economic behavior and caring economic attitudes among fifth-grade students. Using a quasi-experimental pretest–posttest control-group design at SDN 19 Kota Bima (2025/2026), 50 students were assigned by intact class to experimental (n = 25) or control (n = 25) groups. Two validated self-report questionnaires measured sustainable economic behavior (25 items, α = .87) and caring economic attitudes (24 items, α = .89), supplemented by a five-dimension performance rubric and structured observation protocol. After eight sessions, posttest scores favored the experimental group: sustainable economic behavior, t(48) = 8.43, p < .001, Hedges' g = 2.14, 95% CI [1.47, 2.81], N-Gain = 0.58 vs. 0.24; caring economic attitudes, t(48) = 7.91, p < .001, Hedges' g = 1.95, 95% CI [1.30, 2.60], N-Gain = 0.61 vs. 0.22. These unusually large effects, together with the single-site sample, intact-group assignment, and the teacher's dual role as implementer and assessor, warrant cautious interpretation. The findings offer preliminary evidence that embedding indigenous Mbojo principles within structured PjBL can shape behavioral and dispositional dimensions of elementary economic learning; multi-site replication with independent assessment is needed before efficacy can be generalized